Transient CD8-memory contraction: a potential contributor to latent cytomegalovirus reactivation. - Campbell, J; Trgovcich, J; Kincaid, M; Zimmerman, P; Klenerman, P; Sims, S; Cook, C (2012)
It is clear that latent CMV can reactivate in immunocompetent individuals, but the mechanism triggering such reactivations remains unclear. Recent clinical data suggest that reactivation can be subverted by CMV-specific T-memory. We therefore monitored CMV-specific T cells in immunocompetent mice with latent mCMV after a known reactivation trigger (LPS). LPS induced transient systemic contraction of mCMV-specific CD8 memory that was followed by transcriptional reactivation. Subsequent recovery of mCMV-specific T cells coincided with resumption of latency. These data suggest that bacterial antigen encounters can induce transient T-memory contraction, allowing viral recrudescence in hosts latently infected with herpes family viruses.